2018
DOI: 10.1111/mmi.14086
|View full text |Cite
|
Sign up to set email alerts
|

An important role for periplasmic storage inPseudomonas aeruginosacopper homeostasis revealed by a combined experimental and computational modeling study

Abstract: Biological systems require precise copper homeostasis enabling metallation of cuproproteins while preventing metal toxicity. In bacteria, sensing, transport, and storage molecules act in coordination to fulfill these roles. However, there is not yet a kinetic schema explaining the system integration. Here, we report a model emerging from experimental and computational approaches that describes the dynamics of copper distribution in Pseudomonas aeruginosa. Based on copper uptake experiments, a minimal kinetic m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 57 publications
(84 reference statements)
2
24
0
Order By: Relevance
“…Treatment of cells for 10 min with 0.5 mM CuSO 4 was chosen to examine effects on the overall Cu homeostasis. We have shown that these conditions raise cellular Cu but do not affect cellular growth rates (15,16). Fig.…”
Section: Copz1 and Copz2 Have Distinct Roles In P Aeruginosamentioning
confidence: 73%
See 2 more Smart Citations
“…Treatment of cells for 10 min with 0.5 mM CuSO 4 was chosen to examine effects on the overall Cu homeostasis. We have shown that these conditions raise cellular Cu but do not affect cellular growth rates (15,16). Fig.…”
Section: Copz1 and Copz2 Have Distinct Roles In P Aeruginosamentioning
confidence: 73%
“…8B). In bacteria, there is a strict cellular Cu quota, about 10 4 atoms per cell (12), half or less are expected to be in the cytoplasm (16). These numbers correlate well with the amount of CopZ2 encountered in the cytoplasm during steady state, 40 fmol of CopZ2/g of Cytoplasmic Cu ؉ distribution in P. aeruginosa total protein.…”
Section: Copz2 Is More Abundant Than Copz1 In Vivomentioning
confidence: 76%
See 1 more Smart Citation
“…Copper homeostasis depends on an intricate network of Cu binding proteins that serve as sensors, chaperones, transporters and dedicated cuproprotein assembly factors (Cobine et al , ; Singleton and Le Brun, ; Arguello et al , ; Stewart et al , ). In combination with Cu storage proteins, initially found only in eukaryotes but now also identified in bacteria (Dennison et al , ; Parmar et al , ), these proteins basically reduce the concentration of free Cu below the detection limit and thus prevent potential toxicity. CopZ‐like Cu‐chaperones have been identified as major determinants for Cu detoxification because they can bind Cu with femtomolar affinity (Xiao et al , ) and can transfer it to P 1B ‐type ATPases for extrusion.…”
Section: Discussionmentioning
confidence: 99%
“…Copper homeostasis depends on an intricate network of Cu binding proteins that serve as sensors, chaperones, transporters and dedicated cuproprotein assembly factors (Cobine et al, 2006;Singleton and Le Brun, 2007;Arguello et al, 2013;Stewart et al, 2018). In combination with Cu storage proteins, initially found only in eukaryotes but now also identified in bacteria (Dennison et al, 2018;Parmar et al, 2018), these A. The cbb 3 -Cox activity in R. capsulatus wild type and mutant cells was determined by the NADI reaction on MPYE plates.…”
Section: Discussionmentioning
confidence: 99%